SOME SACRED SITES OF PURI TOWN OF ODISHA IN EASTERN INDIA: A HISTORICAL ANALYSIS - Mohapatra, Ratnakar (International Journal of Psychosocial Rehabilitation, 2020)
The place of Puri town is famous for its historic antiquities and religious sanctuaries in Eastern India. This place is also well-known throughout the world for the notable temple of Lord Jagannatha. Though the temple of Lord Jagannatha is regareded asan important sacred shrine of Puri town, but some other minorsacred sites of this town also some times possess same religious sanctity like the shrine of Lord Jagannatha.As a sacred place, this ancient town has been maintaining its highest pitch of glory from time immemorial to till today.In Odisha, Goddess Vimala is popularly known as Pada-Pitheshvari of the Puri town. The spot of Ratnasimhasana of Lord Jagannatha has been considering by pilgrims as the holiest place of Puri town. It is called “Antarvedi”, which is very rare sacred place in the world. The next important shrine in respect of sacredness at Puri town after the celebrated temple of Lord Jagannatha is the Gundicha temple or Gundicha Ghara. Anothersacred site of Puri town is Koili Vaikuntha of the Jagannatha temple complex. So, from the cultural point of view, the Puri town is very interesting area for the study of scholars and historians.The aim of this paper is to study briefly the relious significance of some sacred sites of Puri town, which are closely attached with the rituals and festivals Lord Jagannatha.Methodologically, both the primary and secondary sources have been used in this article to access the historical and religious significance of some sacred sites of Puri town of Odisha in Eastern India.